Xanthosoma gratiae (Araceae), a new species from the cordillera Chongón-Colonche in coastal Ecuador - Cornejo, Xavier; Croat, Tom (Phytotaxa, 2022)
Xanthosoma gratiae, a new species of Araceae endemic to the seasonally dry forests of cordillera Chongón-Colonche in coastal Ecuador, is here formally described and illustrated.